A bit system that guarantees better accuracy for monopulse antenna detection systems. - Harbater, Zelman; Margalit, Avigdor
Accurate integration and calibration of well-designed components can compensate for time-varying errors in a monopulse antenna system. A switchable four-port bit system, using a balanced four-way splitter and four balanced, electronically controlled, fast switches, make it possible to know the signal location measured by the monopulse antenna with very great accuracy in the presence of these errors.
Keywords: Monopulse antennas; Monopulse radar; Direction of arrival estimation